2008
DOI: 10.1111/j.1540-8167.2008.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of 2:1 AV Block: Long QT Syndrome

Abstract: A 6-year-old female with congenital long QT syndrome (LQTS) presented to the hospital with recurrent syncope. She had frequent episodes of Torsade de pointes (TdP) that occurred at night during the hospital stay. The Figure shows interesting recordings from her telemetry monitor. In panel A, on first glance, the patient seemed to be in sinus bradycardia with a heart rate (HR) of 48 beats per minute (bpm) with abnormally long QT interval of 840 ms and bifid T waves. After a closer look, it became clear that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, a few case reports also described true infranodal AV block in these patients (16,31). Despite the relatively infrequent overall occurrence of AV conduction abnormalities (30), they are clearly associated with a poorer prognosis. In neonates, AV block has been associated with an elevated risk of arrhythmia and is more frequent in patients with mutations in HERG, particularly within the pore region (18,27).…”
mentioning
confidence: 99%
“…However, a few case reports also described true infranodal AV block in these patients (16,31). Despite the relatively infrequent overall occurrence of AV conduction abnormalities (30), they are clearly associated with a poorer prognosis. In neonates, AV block has been associated with an elevated risk of arrhythmia and is more frequent in patients with mutations in HERG, particularly within the pore region (18,27).…”
mentioning
confidence: 99%
“…‘Pseudo’ or functional AVB in LQTS is primarly due to markedly prolonged QTc interval. When every other P wave reached the His-Purkinje system or ventricular myocytes, they were most likely still in repolarisation and thus refractory, so that the electrical impulse could not propagate from the atria to the ventricles [ 17 ]. In 1999, Pruvot et al demonstrated electrophysiological features of a patient with congenital LQTS with episodes of true 2:1 AV block, in which the block was seemingly associated with a general disturbance of electrogenesis that caused prolongation of the refractoriness of muscle and conduction structures.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiographic (ECG) manifestations of long QT syndrome are prolonged QT more than 470 milliseconds, T wave alternans, polymorphic ventricular tachycardia (VT), and, rarely, 2:1 atrioventricular (AV) conduction. [1][2][3] Case Report A 3-month-old child was referred to us with a history of shortness of breath for cardiac evaluation. She was evaluated with ECG revealing prolonged QT with QTc of 440 milliseconds and 2:1 AV conduction (►Fig.…”
Section: Introductionmentioning
confidence: 99%